2004
DOI: 10.1001/archinte.164.20.2241
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Diagnosis of Chronic Fatigue Syndrome

Abstract: Most cases of CFS in the population are unrecognized by the medical community; persons diagnosed as having CFS may be different from persons with CFS in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 15 publications
2
45
0
2
Order By: Relevance
“…These problems may in large part explain why only 50% of individuals with CFS have consulted a physician for their illness and fewer than 20% of people with CFS have been diagnosed and treated for the illness [8,9]. Educating providers concerning CFS should improve identification, diagnosis, and management of CFS, but educational activities must be based on providers' current knowledge, attitudes, and beliefs in order to target major current weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…These problems may in large part explain why only 50% of individuals with CFS have consulted a physician for their illness and fewer than 20% of people with CFS have been diagnosed and treated for the illness [8,9]. Educating providers concerning CFS should improve identification, diagnosis, and management of CFS, but educational activities must be based on providers' current knowledge, attitudes, and beliefs in order to target major current weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we are aware of no published studies of CFS that have utilized multiple-night polysomnography, nor are we aware of any published studies that address sleep pathology in a population-based sample of persons with CFS. Because an overwhelming majority of persons with CFS remain undiagnosed [4,18], results of studies on CFS patients identified through physician practices may not be generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…Although not all persons suffering from CFS seek allopathic care [6,7], standard regimens of therapy include cognitive behavioral therapy, varying forms and regimens of exercise, and enhancement of coping skills, while caregiver prescribed or self-administered medication use remains common [8,9]. Recent increase in use of complementary and alternative medicine therapy (CAM) in various forms by the population at large [10-13] as provided by naturopaths, chiropractors, social workers, nutritionists, and acupuncturists, and others, has also been observed among patients with CFS [14-16].…”
Section: Introductionmentioning
confidence: 99%